Response of lettuce (Lactuca sativa L.) plants to replacement of mineral fertilizers to substituted for compost tea - Tarek M. Younis; Doaa A. M. Gad; Fatma S. Moursy; Ihab I. Sadek; Muhammad Jamil3 (Indus Journal of Bioscience Research, 2023)
Background: Lettuce (Lactuca sativa L.) is a widely cultivated leafy vegetable belonging to the Asteraceae family Growth, productivity and quality of lettuce plants Objectives: (Lactuca sativa L.) were evaluated under circumstances of depending on "compost tea", "compost tea + molasses" and "compost tea + bacterial inoculation" as sources for fertilization compared to mineral fertilizers. Methods: The experiment was conducted at Central Laboratory for Agricultural Climate (CLAC), Agricultural Research Center (ARC), Dokki, Giza. Seedlings of lettuce (Lactuca sativa L. c.v Iceberg) were transplanted at the 15th of October through 2019/2020 and 2020/2021 seasons. Results: Obtained results confirmed the ability of "compost tea + bacterial inoculation" followed by "compost tea + molasses" and then chemical fertilizer ranked in the third order as a sole fertilizer for lettuce to enhance plant height, number of leaves per head, head length, head diameter, SPAD reading, head volume, average head weight, total heads yield/m2 and content of nitrogen, phosphorus, potassium, calcium and magnesium and ascorbic acid (Vitamin C) in leaves. While, reduced nitrate content in leaves. Conclusion: Applied "compost tea + bacterial inoculation" and "compost tea + molasses" can considered as one of ways to replacement of mineral fertilizers